Roles and training needs of library support staff in Singapore school libraries. - Gee, Miaw Miin. (2008)
In recent years, many changes have taken place in schools and school libraries in Singapore. The roles of the school library and the school librarian have also been examined in this context of change. This research was conducted to examine the roles of a support staff in a school library in Singapore, to analyze these roles, and through that analysis draw attention to competencies and knowledge needed to perform these roles.